Application of Dual Lead Cylindrical Worm in Equipment Renovation - Zhang Leile; Zhang Dewei; Lu Zhihui; Qiao Yongqiang; You Guangfei (Jixie chuandong)
The dual lead cylindrical worm drive is suitable for high precision indexing and rotary servo axis etc engineering applications。In the light of renovation requirements of a wind tunnel mechanism,based on the analysis of the equipment characteristics and the characteristic of existing drive mechanism,the existing mechanism is replaced by using the dual lead cylindrical worm. The related key point design is analyzed,the new mechanism obtains good use effect.